2020
DOI: 10.14336/ad.2019.0605
|View full text |Cite
|
Sign up to set email alerts
|

Remote Ischemic Conditioning Improves Attention Network Function and Blood Oxygen Levels in Unacclimatized Adults Exposed to High Altitude

Abstract: Remote ischemic conditioning (RIC) confers protection on major organs from hypoxic/ischemic injuries; however, its impacts on attention network function and blood oxygen levels in unacclimatized adults exposed to high altitudes have yet to be elucidated. In this study, we recruited 120 healthy male volunteers, of which one was exposed to high altitude and the other was exposed to low altitude. The two cohorts were further divided into RIC and sham control groups. The attentional network test (ANT) was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…A cohort study of 41 volunteers [21 in high altitude group (5050 m) and 20 in control group (1030 m)] showed impaired attention and executive functions (Pun et al 2018a) as well as increased reaction time (Pun et al 2018b) after acute hypobaric hypoxia. Furthermore, concentration (de Aquino Lamos et al 2012), alertness (Li et al 2020), verbal and visual memories, and cognitive flexibility were also injured after acute hypoxic exposure (Turner et al 2015). Dramatically, as to verbal memory, the proper names were more likely to be affected than the common ones (Pelamatti et al 2003).…”
Section: Acute High Altitude Hypoxiamentioning
confidence: 99%
“…A cohort study of 41 volunteers [21 in high altitude group (5050 m) and 20 in control group (1030 m)] showed impaired attention and executive functions (Pun et al 2018a) as well as increased reaction time (Pun et al 2018b) after acute hypobaric hypoxia. Furthermore, concentration (de Aquino Lamos et al 2012), alertness (Li et al 2020), verbal and visual memories, and cognitive flexibility were also injured after acute hypoxic exposure (Turner et al 2015). Dramatically, as to verbal memory, the proper names were more likely to be affected than the common ones (Pelamatti et al 2003).…”
Section: Acute High Altitude Hypoxiamentioning
confidence: 99%
“…However, to data, there is no direct evidence of the improvement of healthy adults’ cognitive control through RIPC treatment, because in these existing studies, RIPC was applied to improve the cognitive control of these individuals who undergoing surgery or in special circumstances. Furthermore, these studies are very scant and their results are inconsistent ( Meybohm et al, 2013 , 2018 ; Hudetz et al, 2015 ; Li et al, 2020 ; Sugimoto et al, 2021 ). For instance, in the investigations by Meybohm et al (2013 , 2018) , the patients who underwent a wide range of cardiac surgery accomplished a Stroop test (a test demanding cognitive control) before and after receiving the RIPC intervention (induced by four cycles of upper-limb ischemia, 5 min), aim to examine the effect of RIPC on reducing postoperative neurocognitive dysfunction, as a result, they failed to demonstrate the efficacy of a RIPC protocol on cognitive control.…”
Section: Introductionmentioning
confidence: 99%
“… Hudetz et al (2015) reported that the cognitive control tested by the Stroop task before and after surgery were not changed in individuals who both accepted and rejected the RIPC treatment (four cycles of brief upper extremity ischemia, 5 min) but found that the RIPC treatment can prevent deterioration of other short-term cognitive abilities, such as non-verbal and verbal memory. Li et al (2020) found that the alertness but not the executive function of attention in the attentional network test (ANT) was changed by RIPC (5 min bilateral upper limbs ischemia and 5 min reperfusion for five cycles, twice a day, for 7 days) in adults unacclimatized to high altitude. In summary, except for the study by Sugimoto et al (2021) , the above four research did not observe the protective effect of RIPC on cognitive control.…”
Section: Introductionmentioning
confidence: 99%
“…[ 31 32 ] Furthermore, unlike exercise, it is a convenient therapy that is easy to administer on sick, recovering stroke patients. [ 26 33 ]…”
Section: Introductionmentioning
confidence: 99%